An Analysis of Digital Talent in Academic Publications Reflection on Malaysia's Digital Transformation Strategies - Fahmy, Syahrul; Deraman, Aziz; Puteh, Mazidah; Nasir, Akhyari; Roslina, Wan; Haslinda, Nurul (International Journal of Integrated Engineering, 2022)
Digital transformation is the integration of Information and Communication Technologies (ICT) into all business areas and affects industries throughout the world. Digital transformation strategies are entrusted to â€œdigital talentâ€, individuals who are technically equipped and well-versed across domains. However, finding the right talent has proven to be a difficult task and unmanageable to some organizations. Not only there is a shortage of talent, digital economy requires a different set of skills from the current labour market has to offer. This paper aims to shed light into this issue through a systematic literature review. In addition, a reflection on Malaysiaâ€™s digital transformation strategies is presented. Results revealed that there is yet a standard definition for digital talent and its meaning varies across organizations and industries. Although generic descriptions are available, there is a lack of specific skill-set associated with digital talent. Main research directions include supporting digital transformation, talent cultivation, talent attraction, and shortage of talent. This paper contributes to the literature by presenting efforts to bridge the digital talent gap from three different perspectives: short-term, medium-term, and long-term measures. Malaysia has mapped its human capital development against the United Nationâ€™s Sustainable Development Goals since 2016 and is in the right path with regards to its digital transformation strategies. Short-term and medium-term measures are being implemented through up-skilling and re-skilling programs whilst long-term measures are underway although the results of digital transformation across industries have yet to be studied extensively.